Heavy metals and potential risks in edible seaweed on the market in Italy. (January 2021) - Filippini, Maria; Baldisserotto, Anna; Menotta, Simonetta; Fedrizzi, Giorgio; Rubini, Silva; Gigliotti, Domenico; Valpiani, Giorgia; Buzzi, Raissa; Manfredini, Stefano; Vertuani, Silvia
Abstract: The seaweed food has always been important in Asia, but recently increased in the Western diet. Superfood known for health benefits and rich in essential elements, can also accumulate high contents of heavy metals and iodine from the environment, becoming a health hazard. In particular for iodine, an appropriate labelling of seaweed is needed to warn the consumer of the potential risks. The aim of the study was to analyze the content of 20 heavy metals in seaweeds, distributed in Italy, by ICP-MS, also determining iodine and arsenic (total and inorganic fraction). A total of 72 samples of European and Asian seaweed of 8 genera were analyzed and the results correlated the content of heavy metals to genus, geographical origin and type of sample; 8.33% of the products lacked in the label of the indications of allergens, while 9.72% had irregularities in the label language. The highest concentration of elements was found in the Rhodophyta. The Aluminum level was the highest in the mixed seaweed (165.39 mg/kg) and for the Cadmium in the Asian seaweed (1.16 mg/kg). The amounts of Iron, Zinc and Magnesium, was highest in the Asian seaweed. The values of Arsenic (total and inorganic contents) were compared with the limits: 2.78% exceeds France and USA limits for inorganic, while higher content of total was found in Phaeophyta, which also showed the highest Iodine content (6770.80 mg/kg) that can be dangerous if not reported correctly in the label. Highlights: Analysis of 20 essential and non essential elements was performed by ICP-MS. Seaweeds are a source of essential dietary elements, particularly Mg and Fe. Found irregularities on the label of seaweeds about the language and allergens. Results obtained from the speciation of arsenic: Phaeophyta had the highest content. Brown seaweeds showed remarkably high values of iodine.